"This illness diminishes me. What it does is like theft": A qualitative meta‐synthesis of people's experiences of living with asthma. (2nd August 2017) - Pickles, Kristen; Eassey, Daniela; Reddel, Helen K.; Locock, Louise; Kirkpatrick, Susan; Smith, Lorraine
Abstract: Background: What matters to people in their everyday experiences of living with asthma is influenced by a diverse range of personal, social, medical and environmental factors. Previous reviews of the asthma literature have largely focused on medical aspects of asthma or specific population groups with particular needs. Objective: To identify, describe and synthesize from the available qualitative literature the views and experiences of adults living with asthma. Method: We systematically searched for qualitative studies reporting on the personal experience of living with asthma. A meta‐synthesis approach was used to analyse and interpret the data. Key themes relating to personal perspectives on asthma were identified and grouped into overarching concepts. Results: We identified 26 studies. There was a paucity of literature on the physical burden of asthma symptoms and the role of social support. Our synthesis generated a central concept of the "work" associated with living with asthma: work was of a personal nature, and at times an intensely emotional experience. Individuals tailored their behaviour in response to demands of the physical and social environment, including interactions with health‐care professionals. Conclusion: This is the first systematic review of the qualitative literature reporting on people's own perspectives of living with asthma. Our findings draw attention to the nuances and sensitivities surrounding patient experiences of self‐management. Medical care is a central plank of managing chronic conditions, but our health‐care systems are now expected to deliver patient‐centred care. Considering the broader aspects of asthma management, beyond that of symptoms and treatment, will help to facilitate comprehensive care.